2015
DOI: 10.1590/s1806-92902015000600004
|View full text |Cite
|
Sign up to set email alerts
|

Economic and socio-environmental performance assessment of beef cattle production systems: a data envelopment analysis (DEA) approach with weight restrictions

Abstract: -This study evaluated the performance of 21 beef cattle modal production systems that conduct only the raising phase. These production systems were developed in 21 municipalities in seven Brazilian states. We used two different DEA BCC models, corresponding to different points of view. Firstly we used an economic model that measured the ability of a production system to generate revenue with the preservation of native forest, using labor, capital, and current spending as inputs. The socio-environmental approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 21 publications
0
10
0
2
Order By: Relevance
“…However, the use of input factor incurred by farmers for beef cattle farm has not been and was not efficient. It was faced to Gomes et al (2015) that pointed out sources of inefficiency in terms of input with low qualification. When properly observed, the application of "Six Right" approach in agribusiness showed that indicators farm scale forage, concentrate, health and labor were in "Moderate" condition.…”
Section: Economic Efficiency Analysis Of Beef Cattle Breedingmentioning
confidence: 99%
“…However, the use of input factor incurred by farmers for beef cattle farm has not been and was not efficient. It was faced to Gomes et al (2015) that pointed out sources of inefficiency in terms of input with low qualification. When properly observed, the application of "Six Right" approach in agribusiness showed that indicators farm scale forage, concentrate, health and labor were in "Moderate" condition.…”
Section: Economic Efficiency Analysis Of Beef Cattle Breedingmentioning
confidence: 99%
“…Variation among cattle farmers occurred basically in the aspect related to physical productivity, which shows that the investments made to increase the efficiency of the systems produced positive responses (GOMES et al, 2015). Alternatively, when the analysis considered economic results, this difference practically disappears between the clusters, especially in the IEL x HEL comparison.…”
Section: Discussionmentioning
confidence: 97%
“…Other studies with a systemic approach may also complement this study, helping to understand the productive effects by improving the indicators in an isolated or simultaneous manner, mainly by including prices and costs. Improving production efficiency would mean not concentrating efforts on a single component, but rather understanding and managing productive activities as a system (Gomes et al, 2015). In this sense, identifying the impact of the changes of the animal production indicators on the productivity of the farming system can help in the definition of strategies and the ordering of investment priorities (Pereira et al, 2016).…”
Section: Discussionmentioning
confidence: 99%